105k views
1 vote
If f(x)=2x^(2)+3 and g(x)=x^(2)-7, find (f-g)(x). A.)3x^(2)-10 B.)3x^(2)-4 C.)x^(2)+10 D.)x^(2)-4

2 Answers

2 votes

f(x)=2x^2+3\\\\g(x)=x^2-7\\\\(f-g)(x)=(2x^2+3)-(x^2-7)=2x^2+3-x^2+7=x^2+10

Answer: C) x² + 10
User Tomas Vana
by
5.4k points
3 votes

Answer:

The answer is C.)x^(2)+10

Explanation:

Given:

F(x)=2x^(2)+3, and

g(x)=x^(2)-7,

In order to find (f-g)(x), we have to subtract g(x) from f(x), thus: f(x) - g(x) = (f-g)(x) = 2x^(2)+3 - (x^(2)-7) = 2x^(2)+3 - x^(2)+7 = 2x^(2)- x^(2)+3+7 = x^(2)+10

User TeaNyan
by
6.1k points